Matrix-isolation FTIR study of azidoacetone and azidoacetonitrile: Spectroscopy in Cryocrystals and Matrices - Frankowski, Marcin; Costa, Maria L.; Beyer, Martin K.; Smith-Gicklhorn, Alice M.; Fox, Brigitte S.; Cordeiro, ,M. Natália D.S.; Barros, Maria T.; Rodrigues, Paula; Algarra, Manuel; Bondybey, Vladimir E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Azidoacetonitrile (N3CH2CN) and azidoacetone (N3CH2COCH3) were studied by matrix-isolation FTIR spectroscopy in solid neon, argon and nitrogen. The IR spectra calculated using the density fuctional theoretical method are discussed in comparison with the experimental data. Significant broadening of the recorded azide bands indicate an awkward fit of these compounds into the solid environment. The strongest absorption is observed for both compounds in the regions of asymmetric and symmetric stretches of the N3 azide group. Strong band splittings in the N3 asymmetricstretch region can be most likely explained by very strong Fermi resonances with the CN stretch and combinations and overtones of the numerous lower frequency vibrational modes.